Editorial Harada dossier - Fernandes, Marcos Aurélio (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2021)
This dossier recalls the thinker father Hermógenes Harada ofm (1928-2009), and his thoughts. It is the gratitude that intones this recall, which is, in itself, a commitment to think. Thinking happens here as an experience of a graced finitude. It's just that to think, we are not enough to ourselves. We always need someone else to provoke us. We need the questioning of what calls us to think. We need dialogue with the other of ourselves and with the other of others as well. As an exercise in finitude, the effort of thinking always takes place in the manner of a graced finitude. Therefore, thinking is always, in some way, giving thanks. And, vice versa, giving thanks is thinking. The thanksgiving comes from a memory of the heart: it is a remembrance. This memory goes back not simply to the past as a fact, but much more to what is still in force in the concentration of its vigour, which is collected and latent, as a possibility of being protected in the unthought, is already launched towards the future, preceding us always again. It is this validity that allows us to respond, again and again, in a creative way, to the call of the future.